Effect of Milk Fat Substitution of Rennet Milk Induced Coagulation on Physico-Chemical Properties - Imène Felfoul; Salwa Bornaz; Wiem Belhadj Hmida; Ali Sahli; Hamadi Attia (Journal of Chemistry)
The objective of this paper was to study the effect of milk fat substitution by (W1/O/W2) multiple emulsions based on olive oil in comparison with full and low-fat milks on milk behavior during rennet coagulation. Therefore, based on the turbidimetric and conductivimetric methods, a follow up of enzymatic coagulation is realized. Drainage of renneted gels was followed by syneresis study and cheese yield. The comparison between the coagulation aptitude of low fat milk and milk-olive oil emulsion showed that the hydrolysis phase extended up to 35 minutes for full fat milk and up to 38 minutes for milk-olive oil emulsion. The transition phase solid/gel was shorter in the case of the whole milk. The reticulation phase was shorter in the case of milk-olive oil emulsion. The milk conductivity depended on the milk richness in fat content. Milk-olive oil emulsion showed the lowest cheese-making yield compared to its full and low-fat counterpart.